A comprehensive review of studies using the Affective Neuroscience Personality Scales in the psychological and psychiatric sciences. (June 2021) - Montag, Christian; Elhai, Jon D.; Davis, Kenneth L.
Highlights: Panksepp's Affective Neuroscience Theory belongs to the most important emotion theories. The present work provides a comprehensive review on studies using the Affective Neuroscience Personality Scales (ANPS). The ANPS aims to assess individual differences in primary emotional systems. The current review covers 17 years of ANPS-research after the first publication of the ANPS in 2003. The ANPS 3.1 is presented in the Appendix of the paper. Abstract: Jaak Panksepp's Affective Neuroscience Theory (ANT) belongs to the most prominent emotion theories in the psychological and psychiatric sciences. ANT proposes the existence of seven primary emotional systems deeply anchored in the mammalian brain. These emotional/motivational systems have been shaped by evolutionary processes and function as tools for survival in mammalian species. The systems are called SEEKING, LUST, CARE, and PLAY, as well as ANGER, FEAR, and SADNESS. Panksepp carved out these emotional systems via means of deep brain stimulation, brain lesion and pharmacological manipulation studies. Davis et al. (2003) designed the Affective Neuroscience Personality Scales (ANPS) against the background of findings from ANT. This self-report inventory is meant to enable researchers to assess individual differences in primary emotional systems. Seventeen years have passed since the first version of the ANPS has been published. Therefore, we now provide a comprehensive overview on studies using the ANPS including work from personality science, psychiatry and the neurosciences.